Comparison of Cardio–Ankle Vascular Index (CAVI) and CAVI0 in Large Healthy and Hypertensive Populations - Yamamoto, Tomoyuki; Maruyama, Mitsuya; Takahashi, Koji; Takata, Masanobu; Shirai, Kohji; Suzuki, Kenji; Tsuda, Shinichi; Shimizu, Kazuhiro (Journal of Atherosclerosis and Thrombosis, 2019)
Aim: The cardio–ankle vascular index (CAVI) represents the blood pressure-independent arterial stiffness from the origin of the aorta to the ankle. CAVI0 has been proposed as a variant index. We aimed to clarify the difference between CAVI and CAVI0 among large populations, and to explore reasons of the difference.Methods: The subjects were 5,293 Japanese healthy and 3,338 hypertensive people. Simple and multiple regression analyses were performed using age, sex, body mass index, systolic, and diastolic blood pressure (Pd) as variables. Sub-group analysis was performed by sex and age. The CAVI values with and without adjustment by reference pressure were also compared.Results: CAVI had a positive correlation with Pd, while CAVI0 had a negative correlation with Pd in the healthy population. The CAVI values of the hypertensive group were higher than those of healthy group in both men and women, but the CAVI0 values in women of the hypertensive group in the 30–39 age group was significantly lower than that of the corresponding healthy group. Differences of CAVI values with or without modification using the reference pressure were 1.09%±1.38% for the healthy group and 3.68%±1.66% for the hypertensive group.Conclusion: CAVI showed the expected values, but CAVI0 showed inexplicable results in the healthy and hypertensive populations. The differences were due to the strong dependency of CAVI0 on Pd. Differences of CAVI values with or without reference pressure were negligible. These results indicate that CAVI obtained by the VaSera system is appropriate, but CAVI0 is not.